Savoirs médicinaux interspécifiques et interactions entre cornacs et éléphants dans le district de Thongmyxay au Laos - Jean-Marc Dubost; Eric Deharo; Sysay Palamy; Chithdavone Her; Chiobouaphong Haekovilay; Lamxay Vichith; Sébastien Duffilot; Sabrina Krief (Revue d'ethnoécologie)
The mahouts and the elephants of Thongmyxay district in Laos form an original hybrid community composed of humans and an animal species represented by both wild and domestic animals (elephants). We investigated in particular the interactions between mahouts' observation of elephants and their own medicinal practices (human and ethnoveterinary), which have been the subject of two previous publications. Based on this material, supplemented by data collected on the status of domestic village elephants and interviews with four local healers, we discuss here with a multispecies approach combining ethnographic data and ethological knowledge, the modalities of construction and possible exchanges of medicinal knowledge between the two species. Elephants have a status characterised by a double hybridity: wild and domestic on the one hand (with ontological circulations from one state to the other), and animal and human on the other. The part of humanity attributed to the elephants is reflected in particular in the self-agency that is recognised in their ability to heal themselves when they are suffering, which leads to the therapeutic use of their dung by Mahouts. The mahouts include in their ethnoveterinary care of the elephants plants that they see the elephants use when they are ill. The medicinal uses they make of some of these plants in their households are more consistent with their observations of these elephant behaviours than it is with the use of the same items by local healers, suggesting a transfer of medicinal knowledge from elephants to mahouts.Since some of the village elephants in Thongmyxay are still periodically released and come into contact with their wild counterparts, the domestication space forms an interface between humans, wild elephants and the forest, and we discuss conversely the possibility of knowledge transfer from mahouts to village elephants through the ethnoveterinary care they receive.This knowledge which is precious for the health and well-being of people and elephants in Laos is threatened by the reduction of the forest cover sheltering the resources used, and by the relocation of village elephants to tourist centres. Thus, emerges the need to think the conservation of the intangible heritage represented by the knowledge of hybrid communities in terms of interspecific heritage, implying that along with the preservation of the ecosystems that host the resources involved in this knowledge, care must be taken to maintain their access to all the populations (human and animal) that use them.